Neuro-glial interactions at the nodes of Ranvier: implication in health and diseases - Devaux, Jérôme J.; Faivre-Sarrailh, Catherine (Frontiers in Cellular Neuroscience, 2013)
Specific cell adhesion molecules (CAMs) are dedicated to the formation of axo-glial contacts at the nodes of Ranvier of myelinated axons. They play a central role in the organization and maintenance of the axonal domains: the node, paranode, and juxtaparanode. In particular, CAMs are essential for the accumulation of voltage-gated sodium channels at the nodal gap that ensures the rapid and saltatory propagation of the action potentials. The mechanisms regulating node formation are distinct in the central and peripheral nervous systems, and recent studies have highlighted the relative contribution of paranodal junctions and nodal extracellular matrix. In addition, CAMs at the juxtaparanodal domains mediate the clustering of voltage-gated potassium channels which regulate the axonal excitability. In several human pathologies, the axo-glial contacts are altered leading to disruption of the nodes of Ranvier or mis-localization of the ion channels along the axons. Node alterations and the failure of action potentials to propagate correctly from nodes to nodes along the axons both contribute to the disabilities in demyelinating diseases. This article reviews the mechanisms regulating the association of the axo-glial complexes and the role of CAMs in inherited and acquired neurological diseases.